Parthenocarpic brinjal (Solanum melongena): a review (Current Horticulture, 2024)
Brinjal (Solanum melongena L.) is very popular vegetable in India and grown as a warm season vegetable crop. It is rich source of antioxidants, minerals and vitamins. The presence of seeds in brinjal fruit is undesirable to consumers and seedless fruits are therefore in demand due to improved flesh quality and suitability for processing. Phytohormones play important role in fruit development through genetic manipulation, leading to seedlessness. With the development of parthenocarpic brinjal, it can now be possible to grow under the protected conditions which ensure safer production of brinjal without using harmful chemicals. This trait is very useful to develop fruits in a particular environment (greenhouse cultivation) which are unfavourable for successful pollination and fertilization. The parthenocarpic trait has been transferred to desirable varieties through crossing that had high yield with favourable fruit quality. A few lines have been developed through interspecific crossing.The exploitation of molecular markers and transgenic technology have been utilized in developing parthenocarpic brinjal with enhanced fruit quality. Therefore, present review is focused on development and potentiality of parthenocarpic brinjal.
Keywords: Brinjal; Parthenocary; Seedless; Variety; Hybrid; Antioxidants; Pollination; Interspecific crossing